Income gaps: Education and inequality - Leone, Julián; Cascio, Jorge Lo (Economics and Business Review, 2020)
The aim of this paper is to analyze the employment-related real income gaps according to the education level reached by the working population during the 1997– 2017 period. Using a panel methodology (pseudo-cohorts) it sums up that throughout recession, employment-related real income gaps by education level are wider, amplifying income inequality. During the economic boom the narrowing of the gap was due to the weak growth in skilled employment that did not manage to recover the pre-crisis values. This phenomenon is typical of a labour market structure with less skilled employment demand than its increasing supply. The employment-related difference in reduction of the real income gaps is exclusively reflected by a decline in employees from the highest education segment. The whole of tertiary education although with less intensity, replicates its trend. Not only educational credentials increase future employment- related income but also starting then not completing a university degree provides a significant disparity. Gender control shows a sharp drop in its determination.